O Rei reina ou governa? O debate entre Paulino José Soares de Souza e Zacarias de Góis e Vasconcelos em torno do Poder Moderador no início da década de 1860 - Liittig, Sávio Medeiros (2023)
The research aims to analyze the discussions about the Power Moderator that took place in the 1860s in Monarchic Brazil. Given this, two important historical agents are mobilized so that, through their works, we can understand the interpretations that both defended about this same device subscribed in the constitutional order of the Empire. Thus, the works Da natureza e limites do poder Moderador (1860), by Zacarias de Góis e Vasconcelos, is apprehended as a liberal interpretation, and Ensaio sobre o direito administrativo (1862), by Paulino José Soares de Souza, is compared as a conservative interpretation of the Power Moderator. With a view to achieving the proposed objectives, the concepts presented by Pierre Bourdieu about the notions of field and political capital and Patrick Charaudeau's work on political discourse helped us to conjecture that both interpretations of the Moderating Power were intended to equip their co-religionists with arguments that served the respective political groups that Zacarias de Góis and Paulino José Soares were part of in the early 1860s.